Pendugaan Nilai Heritabilitas Bobot Badan pada Sapi Bali di BPTU-HPT Denpasar-Bali - Andara, Dhita Indah; Setiaji, Asep; Edy Kurnianto (Jurnal Sain Peternakan Indonesia, 2024)
Estimating heritability values can be used to implement selection programs and evaluate more targeted breeding programs in Bali cattle. This study aims to estimate the heritability value of birth weight, weaning weight and yearling weight of Bali cattle at Balai Pembibitan Ternak Unggul dan Hijauan Pakan Ternak (BPTU-HPT) Denpasar Bali. The research material used is the recording data of 500 Bali cows originating from 24 males  (sire)with 500 Bali cows (dam) that produce offspring of as many as 500 calves. The data was secondary data, obtained by taking records of body weight data, including birth weight, weaning weight, and yearling weight, along with pedigree data of Bali cattle raised from 2017 to 2021 at BPTU-HPT Denpasar. Estimating the heritability value is done using a one-way unbalanced layout model. The results showed that the heritability values of birth, weaning, and yearling weights were 0.25±0.09, 0.23±0.08, and 0.16±0.07, respectively. Based on these results, it can be concluded that the heritability value of birth weight, weaning weight and yearling weight in BPTU-HPT Denpasar Bali is included in the moderate category so that it can be used as a selection guide to increase the productivity of Bali cattle as local Indonesian cattle.